Industrial structure and concentration in Malaysian manufacturing industry - Abdullah, Muhammad Ridhuan Bos; Abdul Jalil, Suhaila (Universiti Utara Malaysia, 2006)
The study uses econometric analysis; the least square method is used to determine factors that influence changes in the level of concentration of the 103 Malaysian manufacturing industries. The result shows that the concentration ratio of the Malaysian industries are rather high when compared with those in most other countries. At the same time our analysis reveals that competition in certain sectors of the Malaysian manufacturing industry have increased over time. Most importantly, the analysis supports the hypothesis that economies of scale are the major source of concentration. Other variables use in determining the industrial concentration is barriers to entry, the size of industry and foreign ownership.